ANALYSIS OF ROASTING TEMPERATURE AND TIME EFFECTS TO THE QUALITY OF THE ROASTED SEEDS OF SIBETANESE SNAKE SKIN FRUIT - Made Anom Adiaksa; Ketut Suherman (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Sibetan is one of the villages in Karangasem Regency. Snake skin fruit in this area has a peculiarity with the name of sugar snake skin fruit. Snake skin fruit plants are one of the seasonal plants, however the fruits also can be harvested in particular months. Dealing with the post-harvest handling for Sibetan Village area, it has been done a lot of product innovations such as making chips, pasta and raw materials of canned fruit sent to the outside of the island. The price for each kilogram of this snake skin fruit species is relatively expensive; it is up to Rp.15.000,00 when it is not in its harvest season, but during harvest season when there is abundant amount of this fruit, the price will be drastically reduced to Rp.500, 00 even unsold. This spurred the creativity of the community to process the snake skin fruit to be materials that have higher selling value. The existence of third parties who are interested to buy the flesh of the fruit as raw material to produce canned food makes the price of the fruit more stable; Rp.2.000,00 for each kilogram. However, this raises the amount of waste from snake skin fruit that has not been utilized, such as the seeds. One of the efforts done in many areas is to make them as raw materials for beverage. The test result obtained from roasting the seeds of snake skin fruit shows that temperature and time affect the quality of the roasted seeds, it can be seen from the colour and aroma compared to the roasted coffee beans. At 80 ° with a time of 40-50 minutes, the cinnamon category was obtained, the light category at 100 ° with 40-50 minutes of roasting, and the Frecnh category at 120 ° with 40-50 minutes of roasting.